CONVENTION REPORT. (The Accounting Review, 1938)
Abstract The article presents a report of the twenty second annual convention of the American Accounting Association. The convention was held in Atlantic City, New Jersey, on December 27-29, 1937. The program of the convention has been given. The various topics to be dealt in the convention are as follows. Accounting in transition, accounting history and education, public aspects of accounting, a critique of the tentative statement of accounting principles and development of accounting principles. The business session was called by the President Jacob B. Taylor on December 28. The first order of the regular business was the reports of officers. The official purposes of the association were named as follows. To encourage and foster research in accounting and to publish or aid in the publication of the results of research. To develop accounting principles and standards, and seek their endorsement or adoption by business enterprises, public and private accountants, and governmental bodies. To promote studies of accounting as an agency of control of business enterprise and economic affairs in general.